Outpatient Department Clinic Management System at Adventist Medical Center Bacolod - Diplomo, Junic B.; Pomperada, Jake R. (Philippine Social Science Journal, 2025)
To address operational inefficiencies at Adventist Medical Center Bacolod, this project developed a hybrid Outpatient Clinic Management System (OCMS) aimed at modernizing manual processes and centralizing patient records. Utilizing the Rapid Application Development (RAD) model to align with user needs, the system significantly improved clinical workflows, resulting in a 35% reduction in waiting times, a 50% increase in record management efficiency, and a 92% user satisfaction rate. This transition not only enhanced service delivery and data security through digitized scheduling and e-prescriptions but also established a scalable framework for digital healthcare adoption. Future iterations could further elevate efficiency by integrating legacy systems, telehealth services, and machine learning analytics.